Experimental Heat Transfer Study On The Shock Absorber Operation - M. S. M., Sani; Che Ku Eddy Nizwan, Che Ku Husin; M. M., Noor (2008)
This paper focused on the experimental heat transfer study on the shock absorber operation. The objective of this study is to analysis the heat transfer rate at surface absorber body. The shock absorber test rig was developed to collect experimental data. This test rig also useful to test and indicates the condition of shock absorber. A new and modify shock absorber twin tube type 1600cc will be used for this experiment. Ethanol and water are using as alternative substance for damping fluid to improve the air gap between the internal and outside body. Ten cycles of bounce and jounce shock absorber operation before heat transfer were measured. The problem of overheating will be effect of damping fluid characteristics and decrease shock absorber performance. However, using additive on damping fluid with water or ethanol will be good substance to improve heat transfer inside the absorber. Ethanol as a substance can be increased heat transfer inside absorber up to 38%. Furthermore, water has a higher thermal conductivity and increasing heat transfer rate better than ethanol; the result shows that using the water can increased the rate of heat transfer up to 45%. Finally, additive with higher thermal conductivity as the substance should give better heat transfer rate from inside absorber to surroundings.